Shona oral art forms in the age of globalisation: reincarnation of the oral prototype - Chigidi, Willie L. (Midlands State University, 2016)
This article examines the ways and conditions under which shona oral art has adapted itself to the realities of globalization. The paper argues that shona oral art has been preserved and will survive the destructive forces of globalization because it has been captured and recorded on paper using the written word. Also, much of this oral art, especially the folktale, has survived because religious institutions have become new popular centres for artistic creativity. In addition, shona oral art has been transformed from a local community art and has become global art through the use of electronic media. Local musicians have also taken shona oral art to the global stage through international tours using the shona language accompanied by music, instrument and dance. The writer tough observes that the relationship between the story teller and the audience has however been completely transformed.